BReast CAncer susceptibility gene 2 deficiency exacerbates oxidized LDL‐induced DNA damage and endothelial apoptosis. Issue 13 (7th July 2020) - Singh, Shweta; Nguyen, Hien; Michels, David; Bazinet, Hannah; Matkar, Pratiek N.; Liu, Zongyi; Esene, Lilian; Adam, Mohamed; Bugyei‐Twum, Antoinette; Mebrahtu, Elizabeth; Joseph, Jameela; Ehsan, Mehroz; et al.
Abstract: Mutations in the tumor suppressor gene BRCA2 (BR east CA ncer susceptibility gene 2 ) predispose carriers to breast, ovarian, and other cancers. In response to DNA damage, BRCA2 participates in homology‐directed DNA damage repair to maintain genome stability. Genome‐wide association studies have identified an association between BRCA2 single nucleotide polymorphisms and plasma‐lipid levels and lipid deregulation in humans. To date, DNA damage, apoptosis, and lipid deregulation are recognized as central pathways for endothelial dysfunction and atherosclerosis; however, the role of BRCA2 in endothelial dysfunction remains to be elucidated. To determine the role of BRCA2 in endothelial dysfunction, BRCA2 was silenced in human umbilical vein endothelial cells (ECs) and assessed for markers of DNA damage, apoptosis, and endothelial function following oxidized low‐density lipoprotein (oxLDL) treatment. OxLDL was found to induce significant reactive oxygen species (ROS) production in BRCA2 ‐silenced ECs. This increase in ROS production was associated with exacerbated DNA damage evidenced by increased expression and activation of DNA double‐stranded break (DSB) marker γH2AX and reduced RAD51‐foci formation—an essential regulator of DSB repair. Increased DSBs were associated with enhanced expression and activation of pro‐apoptotic p53 and significant apoptosis in oxLDL‐treated BRCA2 ‐silenced ECs. Loss of BRCA2 in ECs was further associated with oxLDL‐induced impaired tube‐forming potential and eNOS expression. Collectively, the data reveals, for the first time, a novel role of BRCA2 as a regulator of EC survival and function in the setting of oxLDL treatment in vitro . Additionally, the data provide important clues regarding the potential susceptibility of BRCA2 mutation carriers to endothelial dysfunction, atherosclerosis, and other cardiovascular diseases. Abstract : We, for the first time, demonstrate that BRCA2 is basally expressed in endothelial cells. Loss of BRCA2 in endothelial cells significantly exacerbated oxLDL‐induced DNA damage and apoptosis indicating that BRCA2‐mutation positive individuals might be at increased risk of endothelial dysfunction–associated diseases.